2005
DOI: 10.1021/jm0504858
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Inhibitor Specificity of the Human Protooncogene Proviral Insertion Site in Moloney Murine Leukemia Virus (PIM-1) Kinase

Abstract: The kinase PIM-1 plays a pivotal role in cytokine signaling and is implicated in the development of a number of tumors. The three-dimensional structure of PIM-1 is characterized by an unique hinge region which lacks a second hydrogen bond donor and makes it particularly important to determine how inhibitors bind to this kinase. We determined the structures of PIM-1 in complex with bisindolylmaleimide (BIM-1) and established the structure-activity relationship (SAR) for this inhibitor class. In addition, we scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
136
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 54 publications
11
136
0
Order By: Relevance
“…This simple and cost-effective screening method allowed us to target both active and inactive kinases and has been shown to provide data that are consistent with orthogonal methods such as isothermal titration calorimetry and enzymatic assays (13,(15)(16)(17). A comparison of T m shift data with IC 50 values of two targets has been included in SI Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This simple and cost-effective screening method allowed us to target both active and inactive kinases and has been shown to provide data that are consistent with orthogonal methods such as isothermal titration calorimetry and enzymatic assays (13,(15)(16)(17). A comparison of T m shift data with IC 50 values of two targets has been included in SI Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The screening data were generated by using a thermal shift assay in which the kinase is stabilized upon inhibitor binding (13,14). This simple and cost-effective screening method allowed us to target both active and inactive kinases and has been shown to provide data that are consistent with orthogonal methods such as isothermal titration calorimetry and enzymatic assays (13,(15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…In this assay, binding affinities are measured indirectly as a function of melting temperature increase (⌬T m ). Several studies have shown that ⌬T m correlates linearly with binding constants of ligands (18). Nucleotides demonstrated no interaction with haspin in the absence of divalent ions (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, small molecule inhibitors of the Pim-1 kinase have been recently described in vitro and in cell-based systems. [33][34][35] Targeting the Pim-1 kinase may be a beneficial addition to a traditional cancer chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%